2022
DOI: 10.1161/strokeaha.122.036889
|View full text |Cite
|
Sign up to set email alerts
|

Use of Lipid-Lowering Drugs After Intracerebral Hemorrhage

Abstract: Hyperlipidemia is common in patients with intracerebral hemorrhage (ICH). Accumulating evidence indicates that patients with ICH are at risk for future hemorrhage recurrence, cardiovascular disease, and ischemic stroke and highlights the importance of secondary prevention of vascular events after ICH. Although the benefits of intensive treatment of hyperlipidemia for reducing ischemic cardiac and vascular events in patients with ischemic stroke are well established, the benefit versus harm in patients with ICH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 75 publications
2
17
0
Order By: Relevance
“…If true, the explanations for these findings are not clear, and it was beyond the scope of this study to further disentangle the presumed benefit of high-intensity statins in reducing non-cardiovascular mortality. Consistent with previous reports, 8,25 we found no association between statin intensity and risk of hemorrhagic stroke.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…If true, the explanations for these findings are not clear, and it was beyond the scope of this study to further disentangle the presumed benefit of high-intensity statins in reducing non-cardiovascular mortality. Consistent with previous reports, 8,25 we found no association between statin intensity and risk of hemorrhagic stroke.…”
Section: Discussionsupporting
confidence: 93%
“…5,7 The SPARCL trial did not investigate intensity or dose-response relations. 6 Additionally, some studies found dose-related side effects of statin use, such as increased risk of hemorrhagic stroke, 6,8 diabetes, impaired liver function, and proteinuria. 5 We therefore examined the effectiveness and safety of initiation of high-intensity statins compared with moderate-intensity statins in patients with ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…7 The present study 5 provides novel insight into the risk stratification of MACE after ICH to help delineate the high-risk group that can then be targeted with optimal secondary stroke prevention strategies. Although trials investigating the safety and efficacy of anticoagulation in ICH survivors with atrial fibrillation 8 and statin therapies in patients with lobar ICH are ongoing, 9 given the emerging association between ICH and future ischemic events even in the absence of atrial fibrillation, trials examining the net benefit of antiplatelet and lipidlowering therapy after ICH, particularly deep hemorrhages, are warranted.…”
Section: + Related Articlementioning
confidence: 99%
“…In this focused updated, Shomanesh and selim review existing literature to outline the competing risks of increased propensity for ICH and benefits of reducing ischemic events of lipid lowering treatments in ICH population. They suggest a treatment paradigm based 8 on available data, but appropriately note that data from dedicated randomized trials are needed to build the necessary evidence to guide optimal lipid-lowering strategy in patients with a history of ICH.…”
Section: Use Of Lipid-lowering Drugs After Ichmentioning
confidence: 99%